Investigating the problems of Indonesian Sea Transportation for an Integrated Information System - Siti Rohajawati (Universitas Islam Sultan Agung, 2018)
The problems of Indonesian sea transportation are seriously need to reveal and solve. Eventhough, the government has a significant role managing the organisation at the executive, managerial, and operational level. They are needed performing of regulations, strategic policy, law arrangements, data and information management, company culture, business process supervision, and functional activities on-the-spot. This research used a system improvement objective that is causal effect analyses, system objectives, and constraints. The data are collected through document studies, interviews, meetings, and discussions. The confirmation and verifications of models were conducted using Focus Group Discussion. The results of analysis indicate that three main problems are structural organisation (executive, management, and operational level), regulations, and integrated of information system. Based on Critical Success Factors, the main barriers were regulations, policies, political will, bureaucracy, organisational governance, infrastructure, and an integrated system. Specifically, the model of value chain and an integrated of information system architecture are recommended.